2009
DOI: 10.1109/memb.2009.934908
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic neural control of cerebral hemodynamics

Abstract: Despite the rich innervation of the cerebral vasculature by both sympathetic and parasympathetic nerves [1], the role of autonomic control in cerebral circulation and, particularly, cerebral hemodynamics is not entirely clear [2]. Previous animal studies have reported inconsistent results regarding the effects of electrical stimulation or denervation on cerebral blood flow (CBF), cerebral pressure-flow relationship, and cerebral vessel response to metabolic stimuli [3]- [5]. Moreover, with the advance of trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 28 publications
2
38
0
3
Order By: Relevance
“…It must be appreciated that factors other than arterial blood gas tensions are known to modulate the effectiveness of dCA, these include: (i) sympathetic activity; (ii) metabolite production; and (iii) perivascular innervation [35][36][37][38][39][40]. Our data do not allow us to comment on the role that these factors played in disrupting autoregulatory processes during maximal apnoea.…”
Section: Discussionmentioning
confidence: 70%
“…It must be appreciated that factors other than arterial blood gas tensions are known to modulate the effectiveness of dCA, these include: (i) sympathetic activity; (ii) metabolite production; and (iii) perivascular innervation [35][36][37][38][39][40]. Our data do not allow us to comment on the role that these factors played in disrupting autoregulatory processes during maximal apnoea.…”
Section: Discussionmentioning
confidence: 70%
“…These models include implicitly the effects of the myogenic mechanism [21], [22], flow-mediated endothelial mechanisms [23] and perivascular innervation [24]–[26] without yet being able to draw a direct correspondence between physiological mechanisms and specific model characteristics. Such input-output models often incorporate end-tidal CO2 measurements to account for the known effects of blood CO2 tension on this physiological process, especially in the low-frequency range from 0.02 to 0.08 Hz [8], [10], [12], [27]–[31]. Previous studies have shown that the characteristics of CFA and CVR are altered by orthostatic stress, hypertension, hypoxia, hypercapnia, head injury, stroke, early Alzheimer’s disease and pharmaceutical interventions that affect the autonomic nervous system or vascular tone [11], [12], [28], [32]–[38].…”
Section: Introductionmentioning
confidence: 99%
“…Such input-output models often incorporate end-tidal CO2 measurements to account for the known effects of blood CO2 tension on this physiological process, especially in the low-frequency range from 0.02 to 0.08 Hz [8], [10], [12], [27]–[31]. Previous studies have shown that the characteristics of CFA and CVR are altered by orthostatic stress, hypertension, hypoxia, hypercapnia, head injury, stroke, early Alzheimer’s disease and pharmaceutical interventions that affect the autonomic nervous system or vascular tone [11], [12], [28], [32]–[38]. Some of the recent findings were made possible by Volterra-type nonlinear modeling with two inputs (arterial blood pressure and end-tidal CO2) [10]–[12].…”
Section: Introductionmentioning
confidence: 99%
“…Состо-яние мозгового кровотока модулируется не только церебральной ауторегуляцией, но и вегетативной нервной системой и артериальным барорефлектор-но-опосредованным контролем в большом круге кровообращения [41]. В ответ на симпатическую ак-тивацию наблюдается вазоконстрикция [42,43]. Це-ребральные механизмы ауторегуляции способны компенсировать потребление кислорода [44], одна-ко повторные эпизоды гипоперфузии приводят к истощению компенсаторных возможностей.…”
Section: патогенез ог при дтлunclassified